Editorial - Armstrong , Anona (Journal of Law and Governance, 2013)
Ethics and Values in the Corporate World A purpose of good governance is to reinforce accountability in organisations, and by doing so to improve their efficiency and endorse an ethical approach to commercial decisions and enterprise. The five papers in this volume of the Journal address values and ethics in relation to these issues.